The "Pepper-Spraying Cop" Icon and Its Internet Memes: Social Justice and Public Shaming Through Rhetorical Transformation in Digital Culture. Issue 2 (3rd April 2018) - Mielczarek, Natalia
Abstract : Within hours of its publication online, the "pepper-spraying cop" image from the Occupy Wall Street movement at the University of California–Davis became an Internet meme. The outraged public manipulated key signifiers of the famous picture, creating hundreds of digital derivatives that offered new takes on what happened. With the use of iconographic tracking and visual rhetorical analysis, the study argues that Internet memes are more than silly jokes or social commentary. Through rhetorical transfigurations, they can deliver social justice and launch public shaming campaigns, serving as online instruments to respond to an off-line event.